2018
DOI: 10.1186/s12885-018-4792-9
|View full text |Cite
|
Sign up to set email alerts
|

A new promising way of maintenance therapy in advanced ovarian cancer: a comparative clinical study

Abstract: BackgroundThere is an urgent need for more novel and efficacious therapeutic agents and strategies for the treatment of ovarian cancer - one of the most formidable female malignancies. These approaches should be based on comprehensive understanding of the pathobiology of this cancer and focused on decreasing its recurrence and metastasis. The aim of this study was to evaluate the efficacy of five-year maintenance therapy with indole-3-carbinol (I3C) as well as I3C and epigallocatechin-3-gallate (EGCG) conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Moreover, recent study has suggested the use of EGCG in combination with indole-3-carbinol for better treatment outcomes in advanced ovarian cancer patients (Kiselev et al, 2018). Currently, a randomized, early phase 1 trial is ongoing to evaluate the chemopreventive effects of Teavigo™ (highly purified and refined green tea extract providing 94% EGCG) (450 mg/PO/day) in colorectal cancer (CRC) patients with curative resections (NCT03072992).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…Moreover, recent study has suggested the use of EGCG in combination with indole-3-carbinol for better treatment outcomes in advanced ovarian cancer patients (Kiselev et al, 2018). Currently, a randomized, early phase 1 trial is ongoing to evaluate the chemopreventive effects of Teavigo™ (highly purified and refined green tea extract providing 94% EGCG) (450 mg/PO/day) in colorectal cancer (CRC) patients with curative resections (NCT03072992).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…Finally, we proceeded with the analysis of the articles studying long-term interventions (Table S3). In these works, we found various publications on different types of cancers: prostate [48,49], breast [37], ovarian [50], and pancreas (pilot [51] and development [52]), and one work on type 2 diabetes mellitus [35] and a letter to the editor [38] as a result of this study.…”
Section: Long-term Studiesmentioning
confidence: 81%
“…The works of Thomson et al [37] on breast cancer and Kiselev et al [50] on ovarian cancer were studies with the highest number of participants and the longest periods of evaluation. Thomson et al [37] studied the effects of diindolylmethane (DIM) + tamoxifen administration for 12 months.…”
Section: Long-term Studiesmentioning
confidence: 99%
“…Ovarian cancer is the most common malignant gynecological cancer and the fifth leading cause of female cancer‐related health problems and deaths all over the world . Maximal cytoreductive surgery followed by platinum‐taxane chemotherapy has been the standard first‐line therapy for ovarian cancer . However, about 80% of advanced ovarian cancers relapse with a more aggressive and drug‐resistant disease .…”
Section: Introductionmentioning
confidence: 99%
“…1 Maximal cytoreductive surgery followed by platinum-taxane chemotherapy has been the standard first-line therapy for ovarian cancer. 2 However, about 80% of advanced ovarian cancers relapse with a more aggressive and drugresistant disease. 3 As with most malignant solid tumors, the formation of large numbers of microvessels constitutes the basis for growth and metastasis of ovarian cancer tumors.…”
Section: Introductionmentioning
confidence: 99%